Reference maintenance in the narratives of Albanian–Greek and Russian–Greek children with Developmental Language Disorder: A study on crosslinguistic effects. Issue 2 (April 2022) - Andreou, Maria; Peristeri, Eleni; Tsimpli, Ianthi Maria
Although a considerable number of studies have shown D(eterminer) elements, i.e. determiners and pronominal clitics, to be particularly vulnerable to impairment in monolingual children with Developmental Language Disorder (DLD), little is known about the use of appropriate or/and grammatically correct referring expressions in the children's narrative production. Grammars of languages that differ in the way they encode and realize their D system may be viewed as the ideal context to disentangle the contribution of language (L1) transfer and morpho-syntactic impairment to reference use in the L2. The aim of the current study is to examine L1 effects in the use of referring expressions of 5- to 11-year-old Albanian–Greek and Russian–Greek children with DLD, along with typically developing (TD) bilingual groups speaking the same language pairs when maintaining reference to characters in their narratives. The three languages differ in their D elements, since Albanian and Greek have morphologically rich D systems in contrast to Russian, which lacks a definiteness distinction. Children produced oral narratives in Greek by using the Greek versions of two stories ( Cat and Dog ) which have been designed within the Multilingual Assessment Instrument for Narratives (MAIN) tool of the COST Action IS0804. Results show that the groups did not differ in referential appropriateness. Regarding grammatical correctness, both groups with DLD produced more ungrammatical forms than TD children, while Russian–Greek children with DLD produced more ungrammatical article-less NPs than the other groups. The overall results reflect the joint contribution of language impairment and L1-specific typological properties in the definite forms used for character maintenance by bilingual children with DLD.